From starburst to quiescence: the rapid evolution of galaxies within the large-scale structure - Wilkinson, Aaron K.R. (2017)
Submillimetre galaxies (SMGs) and post-starburst (PSB) galaxies are among the most rare and interesting classes of objects in extragalactic study. SMGs are extremely active dust-obscured galaxies in the early Universe, forming stars with an immense rate of up to 1000 solar masses per year. PSB galaxies are characterised by strong Balmer absorption lines in their spectra, consistent with a recent burst of star formation before being rapidly quenched. The origin of both of these objects and how they relate to the more common populations of red-sequence and blue-cloud galaxies remain elusive. My thesis involves weighing the dark matter halos inhabited by these rare galaxies, by investigating their clustering at 0.5<z<3.5. To achieve this, I use data from two deep large-scale near-infrared surveys: the UKIDSS Ultra Deep Survey (UDS) and the Cosmic Evolution Survey (COSMOS). The former survey is complemented by 850 micron maps from the SCUBA-2 Cosmology Legacy Survey, from which SMGs are identified. Both UDS and COSMOS fields also benefit from a wide range of multi-wavelength imaging, vital for the photometric selection of PSB galaxies.